2018
DOI: 10.1016/j.infbeh.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Early life experiences: Meaningful differences within and between families

Abstract: Previous research has focused on differences in early life experiences that occur between families and their impact on children's development. However, less is known about the variations in early life experiences that occur within families. Here, 53 British mothers (mean age = 34.46 years; SD = 4.35) of newborn infants (mean age = 1.68 months, SD = 0.96) used a smartphone application (app) to repeatedly rate their wellbeing and support and to report their baby's and their own dietary and sleeping patterns (4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Even within WEIRD societies, child-centered parenting may not be representative of the majority (Brown et al, 2008;Ganz, 2018). For instance, mothers with low family income or many children are less likely to describe the ideal mother as highly sensitive (Mesman et al, 2016), and behavioral studies have shown large variation in social and cognitive input within communities (Kuchirko & Tamis-LeMonda, 2019), and between and even within families (von Stumm & Latham, 2018). In short, convergent evidence suggests that, rather than "expecting" high levels of caregiver investment in a specific form (e.g., sensitive responsiveness), infants and children may have evolved adaptations for dealing with a wide range of quantity and quality of caregiving experiences.…”
mentioning
confidence: 99%
“…Even within WEIRD societies, child-centered parenting may not be representative of the majority (Brown et al, 2008;Ganz, 2018). For instance, mothers with low family income or many children are less likely to describe the ideal mother as highly sensitive (Mesman et al, 2016), and behavioral studies have shown large variation in social and cognitive input within communities (Kuchirko & Tamis-LeMonda, 2019), and between and even within families (von Stumm & Latham, 2018). In short, convergent evidence suggests that, rather than "expecting" high levels of caregiver investment in a specific form (e.g., sensitive responsiveness), infants and children may have evolved adaptations for dealing with a wide range of quantity and quality of caregiving experiences.…”
mentioning
confidence: 99%
“…Parental questionnaires asking for reports of young children's behavior at home have been used successfully in previous research (e.g., Hammond et al., 2017). In particular, the ambulatory assessment approach using participants' smartphones to collect data (e.g., Fahrenberg et al., 2007; Miller, 2012; Trull & Ebner‐Priemer, 2013) has yielded promising results regarding the study of a wide range of naturally occurring behaviors during childhood (e.g., Dirk & Schmiedek, 2017; von Stumm & Latham, 2018). Ambulatory assessment constitutes a minimally invasive method that has thus far often been used in clinical psychology to monitor patients' experiences of symptoms in their daily lives.…”
Section: Introductionmentioning
confidence: 99%